PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN SARANA PRASARANA SEKOLAH TERHADAP PROFESIONALISME GURU SMK NEGERI KECAMATAN PINGGIR KABUPATEN BENGKALIS - Jumeri, Jumeri; Suanto, Elfis; Yuanita, Putri (Jurnal JUMPED (Jurnal Manajemen Pendidikan), 2023)
The purpose of this study was to analyze the influence of the principal's leadership and infrastructure on the professionalism of teachers at SMK Negeri Pinggir, Bengkalis Regency. The background of this research is based on the description of the professionalism of teachers in Pinggir District State Vocational Schools that have not been maximized and other factors that influence teacher professionalism, namely the leadership of the principal and infrastructure. The type of research conducted is survey research with a quantitative research approach. The population in this study were all teachers of State Vocational High Schools located in the suburbs of Bengkalis Regency, amounting to 80 people who were divided into 2 State Vocational Schools in Pinggir District. While the sample of this study were all teachers of Pinggir State Vocational School, amounting to 80 people. Data collection techniques, namely documentation and questionnaires. Analysis of the data used is descriptive statistics and inferential statistics. The results of the study show that the leadership of the principal and infrastructure has a significant effect on the professionalism of teachers at State Vocational Schools, Pinggir District, Bengkalis Regency. The magnitude of the influence between the variables of the principal's leadership and infrastructure on teacher professionalism was obtained at 40.77%. the remaining 59.3% is determined by other factors that are not part of this study.